Translation techniques of street food-related culture-specific items of Malacca - Hongxiang, Zhu; Hoon, Ang Lay (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to identify the translation techniques of culture-specific items and tendencies of culture preservation. While culture-specific items and translation have long been discussed, study on how street food-related culture-specific items are translated is still scanty. This qualitative case study focuses on street food names to describe and gain a holistic understanding of the translation techniques on culture-specific items. Purposive sampling is employed to collect data from Jonker Street in Malacca. A sample of 232 name pairs of street food are collected in this study. The collected primary data is analyzed based on modified Josep Marco’s (2019) taxonomy of translation techniques: borrowing, literal translation, neutralization, amplification and compression, adaptation, omission. The result reveals that the borrowing and literal translation techniques are mostly adopted in translating street food-related culture-specific items in Malacca. The translation of street food- related culture-specific items in Malacca tends to preserve source culture. In conclusion, modified Josep Marco’s taxonomy of translation techniques can be used in identifying translation techniques between Chinese and English and help to recognize the tendency of culture preservation.